ANALISIS PENGENDALIAN INTERN PADA SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER - Wasiyanti, Sri (www.bsi.ac.id, 2014)
Of information is the most important part of a system.The system that managed well so that reliable information can be produced.Financial report is one example of information used by the internal and ekstern to assess an enterprise.The reliability of in a financial filing very determined by good or whether or not an accounting system applied to the company.Hence researchers do research by the title internal control the the information system accounting dna-based computer to increase the internal control.Based on the title of research over the researchers explore internal control this as a whole includes the implementation of the internal control in general and control the application of so that it can be increased its application in the future.Keywords: the system of internal control, information systems of accounting